From Excess to Shortage - Recent Developments in the Danish Labour Market - Torben Andersen (Center for Economic Studies and ifo Institute (CESifo), 2003)
The Danish labour market has undergone a remarkable change during the 1990s with a reduction of the unemployment rate from about 12 per cent in 1993 to less than 6 per cent at the turn of the century. This reflects both a turn in the business cycle but also structural changes related to shifts in labour market policies. The focus of labour market policies has been changed from passive measures towards more active measures and there has also been important changes in the unemployment insurance system. This paper offers an overview of the developments in the Danish labour market during the 1990s, and reviews the major policy shifts, as well as possible explanations of the remarkable reduction in unemployment.
Keywords: J30; J60; 330